2019
DOI: 10.7150/thno.33872
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-derived exosomes as a nanotherapeutic agent for amelioration of inflammation-induced astrocyte alterations in mice

Abstract: Mesenchymal stem cell-derived exosomes (MSC-Exo) have robust anti-inflammatory effects in the treatment of neurological diseases such as epilepsy, stroke, or traumatic brain injury. While astrocytes are thought to be mediators of these effects, their precise role remains poorly understood. To address this issue, we investigated the putative therapeutic effects and mechanism of MSC-Exo on inflammation-induced alterations in astrocytes.Methods: Lipopolysaccharide (LPS)-stimulated hippocampal astrocytes in primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
188
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(191 citation statements)
references
References 65 publications
3
188
0
Order By: Relevance
“…Accumulating evidence suggest that MSC-exos possess superior safety profile, anti-inflammatory effects, minimal immunogenicity, and low risks of tumor formation [99,156,157]. Unlike MSCs, exosomes cannot replicate, which contribute to avoiding uncontrolled division.…”
Section: Advantages and Challenges For Msc-exos In The Application Ofmentioning
confidence: 99%
“…Accumulating evidence suggest that MSC-exos possess superior safety profile, anti-inflammatory effects, minimal immunogenicity, and low risks of tumor formation [99,156,157]. Unlike MSCs, exosomes cannot replicate, which contribute to avoiding uncontrolled division.…”
Section: Advantages and Challenges For Msc-exos In The Application Ofmentioning
confidence: 99%
“…Of note, in ASD, peripheral blood mononuclear cell (PBMC)-derived macrophages show dysregulation in an in vitro cellular model [56]. In addition, exosomes exert anti-inflammatory activities in neurological diseases, likely due to stimulation of anti-inflammatory cytokines production [57]. In this way, their application in resolving the strong ASD-associated pro-inflammatory state could be desirable.…”
Section: The Capacity Of Exosomes To Address Asd-related Issuesmentioning
confidence: 99%
“…Exosomes are a class of membrane lipid vesicles with a diameter of between 40 and 100 nm (9), containing messenger RNAs, microRNAs, proteins, and liposomes, which can involve in cell-to-cell communication and targeting cells (10). Exosomes can be widely extracted in the blood, urine, cerebrospinal fluid, and other bodily fluids (11,12). And the number and composition of exosomal miRNAs are different between epileptic or depressive patients and healthy individuals (13).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes, as a new type of cell communication vector, can participate in the regulation of central nervous system neuroinflammation by specific binding with target cells of nervous system, reduce neuronal loss and so on (20). For example, researchers treated pilocarpine-induced epilepsy models with stem cell-derived exosomes and found that this exosomes alleviated inflammation and improved status epilepticus-induced learning and memory impairment in mice by targeting hippocampal astrocytes (11).…”
Section: Introductionmentioning
confidence: 99%